Contraception modes: increasing women's commitment to modern combined oral contraceptives with the shortest possible hormone-free interval - Elena N. Andreeva; Ekaterina V. Sheremetyeva (IP Berlin A.V., 2020)
By definition, contraception is the prevention of pregnancy and infection from diseases by mechanical, chemical and other contraceptives and methods. According to World Health Organization (WHO) statistics, up to 40% of women of reproductive age still believe that their needs for family planning services are not met during counseling. When recommending contraception, it is important to consider: the characteristics of the potential consumer, the underlying risk of the disease, possible undesirable drug reactions of various drugs, the cost, availability and preferences of the woman herself. Women are often forced to abandon the use of a contraceptive method in connection with adverse events, for example, when using combined oral contraceptives (COCs), they may feel worse (headaches, mood lability, weight gain, swelling, decreased libido) in a hormone-free interval, especially with the reception mode 21/7. Lack of contraception can lead to an increased risk of an unwanted pregnancy. According to statistics in the Russian Federation in 2018, the absolute number of abortions amounted to 567 183, which, according to the UN classification, corresponds to the average level (level of abortion rate per 1000 women of childbearing age). According to clinical practice, there is a relationship between deterioration of well-being and the duration of the hormone-free interval. At the moment, in our country there is the only COC, which has a hormone-free interval of 2 days, containing bioidentical estrogen estradiol valerate and dienogest. According to the Cochrane Library, COCs with a short hormone-free interval are most effective in relation to the clinical manifestations of the estrogen withdrawal syndrome. WHO calls on clinicians to raise womens awareness of modern methods of contraception.